Варианты построения емкостных измерителей радиального биения валов электрических машин - Новик, А.И.; Неболюбов, Е.Ю.; Левицкий, А.С.; Архипова, Л.В. (Технічна електродинаміка, 2012)
Substances of task of measurement of runout of rotating shafts of machines are shown. Variants of structure electronic circuits of electronic measuring converters of radial runout with capacitive sensor are proposed.